KONSEP PERENCANAAN PERSPEKTIF AL-QURAN DALAM TAFSIR AL- AZHAR DARI BUYA HAMKA - Siti Trizuwani; Hamidullah Mahmud (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
The importance of planning is the existence of planning / planning possibilities that will occur for an activity and work in the future The relevance of the concept of planning in the modern era faces various significant challenges and opportunities. This research is included in the type of qualitative research, more precisely descriptive qualitative with library research data sources or literature, whose findings are not achieved by statistical procedures. The purpose of this research is to explore and analyse the concept of planning from the perspective of the Quran contained in Tafsir Al-Azhar. The results of this study indicate that some of the challenges are: rapid technological transformation; global uncertainty; stakeholder participation; limited resources. While the opportunities are: innovation in the planning process; sustainable approach; community involvement; flexibility and resilience. It can be concluded by the researcher that although there are various challenges in maintaining the relevance of planning concepts in modern times, there are also many opportunities for innovation and development. The key to success lies in adaptability and the adoption of more inclusive and sustainable approaches